Partial Spectral Flatness Measure for tonality estimation in a filterbank-based psychoacoustic model for percep tual audio coding - Taghipour, Armin; Jaikumar, Maneesh Chandra; Edler, Bernd; Stahl, Holger (134th Audio Engineering Society, 2013)
Perceptual audio codecs use psychoacoustic models for irrelevancy reduction by exploiting masking effects in the human auditory system. In masking, the tonality of the masker plays an important role and therefore should be evaluated in the psychoacoustic model. In this study a partial Spectral Flatness Measure (SFM) is applied to a filter bank-based psychoacoustic model to estimate tonality. The Infinite Impulse Response (IIR) band-pass filters are designed to take into account the spreading in simultaneous masking. Tonality estimation is adapted to temporal and spectral resolution of the auditory system. Employing subjective audio coding preference tests, the Partial SFM is compared with prediction-based tonality estimation. <br